Ab Initio Study of Electron Capture in Collisions of Protons with CO2 Molecules - Luis Méndez; Ismanuel Rabadán (Molecules)
Ab initio calculations of cross sections for electron capture by protons in collisions with CO2 are carried out at energies between 100 eV/u and 50 keV/u, employing a semiclassical method within the Franck–Condon framework. The scattering wave function is expanded in a set of ab initio electronic wave functions of the HCO2+ supermolecule. The calculation is performed on several trajectory orientations to obtain orientation-averaged total cross sections. A two-state model with an exponential interaction between the entrance and the lowest charge transfer channel is proposed to describe the main aspects of the charge transfer process and to estimate the precision of the molecular expansion. The symmetry of the HOMO <semantics>πg</semantics> of CO2 is relevant to choose the signs of the molecular functions and to set up the orientation average of the cross sections. Very good agreement is found with the experimental charge transfer cross sections.